Inhibition of influenza virus replication by Apiaceae plants, with special reference to Peucedanum japonicum (Sacna) constituents. (28th June 2022) - Kanazawa, Ryoko; Morimoto, Ryosuke; Horio, Yuka; Sumitani, Hidenobu; Isegawa, Yuji
Abstract: Ethnopharmacological relevance: Apiaceae plants possess various pharmacological properties, such as antimicrobial, antioxidant, hypoglycemic, hypolipidemic, anxiolytic, analgesic, anti-inflammatory, anti-convulsant, and anti-cancer activities; however, data on their antiviral activity are limited. Peucedanum japonicum, also known as Sacna, is a plant used as food and as a traditional folk medicine for treating coughs. However, the active components in the leaves of this plant are yet unexplored. Aim of the study: To assess Apiaceae plants, especially Peucedanum japonicum, with anti-viral activity, and the function and antiviral potential of Sacna constituents, considering the emergence of influenza virus strains resistant to the currently available drugs. Materials and methods: We prepared grinds of the freeze-dried leaves and roots of the Apiaceae family and the hot water extracts. The antiviral activities of the extracts were determined by focus formation reduction assay. In the time-of-addition assay, the test medium containing Sacna extract at 2 mg/mL was added at −1 to 0 h (adsorption) or from 0 to 4, 4 to 8, or 0 to 8 h (replication). The Sacna extract was separated by reversed-phase flash column chromatography using an Isolera Spektra system. The antiviral activity of each fraction was then determined using the focus formation reduction assay. The active fraction was analyzed using an LC20ADXR high performance liquid chromatography system equipped with a microTOF-QII quadrupole time-of-flight tandem mass spectrometer. Results: All examined extracts of Apiaceae plants showed anti-influenza activity. Sacna extract most strongly inhibited the replication of influenza viruses. Individual components of Sacna possess antiviral activities against the influenza A/PR/8/34 virus. Sacna was found to inhibit the multiplication of A (H1N1 and H3N2) types and B types of influenza viruses, including amantadine-resistant and oseltamivir-resistant viruses. Sacna also inhibited influenza infection during viral replication. However, Sacna did not inhibit influenza infection during cell adsorption and did not suppress hemagglutination inhibition or cell fusion. Further, our findings suggest that the antiviral compounds in Sacna include flavonoids (quercetin and luteolin) and other polyphenols (caffeic acid, hymecromone, and umbelliferone). Although several effective compounds in Sacna inhibit multiple steps of viral replication, caffeic acid, which was increased by heat treatment at the time of extraction, significantly inhibited only the late period of viral growth, similar to the Sacna extract, indicating that it is the major component responsible for the antiviral activity of Sacna. Conclusions: Apiaceae plants possess antiviral activity. Caffeic acid is the major component responsible for the antiviral activity of Sacna. To our knowledge, this is the first report regarding the anti-influenza virus activity of Sacna. Overall, these results indicate that Sacna has potential as a novel treatment against influenza A and B viruses. Graphical abstract: Image 1 Highlights: Peucedanum japonicum, known as Sacna, is a plant used as food and a folk medicine. We examined the antiviral potential of Sacna constituents against influenza viruses. Flavonoids and other polyphenols were determined as the active components. Sacna extract was found to inhibit the multiplication of influenza viruses. Sacna has potential as a novel treatment against influenza A and B viruses.